Enzymatic fuel cells : from fundamentals to applications - Luckarift, Heather R., 1971-; Atanassov, Plamen B., 1962-; Johnson, Glenn R., 1967- (Hoboken, New Jersey : Wiley, 2014)
'Covering the fundamentals of enzymatic fuel cells as well as their design, optimization, integration, and future trends, Enzymatic Fuel Cells provides practical applications of enzymatic fuel cells, including their use in biomedical applications and as power supplies for small portable power devices. Blending introductory reading with a concise scheme of illustration and a special emphasis on methodology of fabrication and testing of enzymatic fuel cells, the book is ideally suited for environmental and chemical engineers, wastewater industry professionals, electrochemists, biologists, and students'--
'The book provides introductory reading with a concise scheme of illustration and with a special emphasis on methodology of fabrication and testing of enzymatic fuel cells. The book addresses these issues in five areas: Introduction to Enzymatic Fuel Cells; Fundamentals of Enzymatic Fuel Cells; Optimizing and Characterizing Biological Catalysis; System Design and Integration; and Outlook to Future Development and Emerging Applications'--
1. Introduction: Enzymatic Fuel Cells : From Fundamentals to Applications -- 2. Electrochemical Evaluation of Enzymatic Fuel cells and Figures of Merit -- 3. Direct Bioelectrocatalysis : Oxygen Reduction for Biological Fuel cells -- 4. Anodic Catalysts for Oxidation of Carbon-Containing Fuels -- 5. Anodic Bioelectrocatalysis : From Metabolic Pathways to Metabolons -- 6. Bioelectrocatalysis of Hydrogen Oxidation/Reduction by Hydrogenases -- 7. Protein Engineering for Enzymatic Fuel Cells -- 8. Purification and Characterization of Multicopper oxidases for Enzyme Electrodes -- 9. Mediated Enzyme Electrodes -- 10. Hierarchical Material Architectures for Enzymatic Fuel Cells -- 11. Enzyme Immobilization for Biological Fuel Cell Applications -- 12. Interrogating Immobilized Enzymes in Hierarchical Structures -- 13. Imaging and Characterization of the Bio-Nano Interface -- 14. Scanning Electrochemical Microscopy for Biological Fuel Cell Characterization -- 15. In Situ X-ray Spectroscopy of Enzymatic Catalysis : Laccase-Catalyzed Oxygen Reduction -- 16. Enzymatic Fuel Cell Design, Operation and Application -- 17. Miniature Enzymatic Fuel Cells -- 18. Switchable Electrodes and Biological Fuel Cells -- 19. Concluding Remarks and Outlook.
'Published simultaneously in Canada'--Title page verso.
Includes bibliographical references and index.
Keywords: Fuel cells; Fuel cells -- Research; Enzymes -- Biotechnology; Electrocatalysis